Pembelajaran Dalam Jaringan (Daring) Mata Pelajaran PAI Siswa Kelas VIII SMP Qu’ran Darul Fattah Bandar Lampung Tahun Pelajaran 2020/2021: Pembelajaran Dalam Jaringan (Daring) - Langgeng Sutopo (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2021)
This research was motivated by the covid-19 pandemic which makes the world of education, especially Indonesia innovate to do Arabic language learning that is implemented online. This study aims determine the effectiveness of inline learning on Arabic language subjects that include the response of students, parents and teachers as well as the difficulties encountered in the implementation of online learning at PAI subjects. The subject in this study is the students of class VIII SMP Qur’an Darul Fattah Bandar Lampung with a total of 36 students. The research method used is descriptive qualitative, data collection techniques are carried out using interview, questionnaires and documentation. The result of the interview and questionnaire distribution was that 75% of parents agreed that online learning was not effectively applied in learning and 50% of parents are dissatisfied with online learning. 69% of students think face-to-face learning is more effective than online learning and ranges from about 50% above who do not like changes in the implementation of learning, while teachers argue that online learning is less effective in applying Arabic language learning because students have difficulty understanding lessons. The biggest difficulty experienced by many types of respondents is the inadequate internet network.